PENGARUH VARIASI PRODUK, VARIASI RASA, DAN HIGIENIS TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO ROTI HANIE BC - Periansah, Denny; Sismanto, Adi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
This research aims to find out which factors most dominantly influence purchasing decisions. The research was conducted from February to June 2024. The sample for this research is consumers who have previously purchased products and know the Hanie BC Bakery. This research used quantitative methods on 125 respondents. The sampling technique is accidental sampling. The analytical method used in this research is a quantitative method with Multiple Linear Regression using SPSS 27 for Windows. Based on the results of multiple linear regression, the regression equation Y = 3.195 + 0.545 (X1), + 0.154 (X2) + 0.293 (X3) was obtained and the coefficient of determination R Square (R2) value was 0.610 or around (61.0%). The research results and hypotheses in this study show that product variation variables, taste variations have a partial or simultaneous positive effect on purchasing decisions at the Hanie BC Bakery.Keywords: Product Variations, Taste Variations, Hygiene and Purchasing Decisions.Pembelian.